A Method for Reducing of the Overall Torsion for Reinforced Concrete Multi-Storey Irregular Structures - Botis, Marius Florin; Cerbu, Camelia (Applied sciences, 2020)
The uneven distributions of mass and stiffness in the case of multi-storey concrete buildings lead to a torsion sensitivity of those civil structures under dynamical loadings like earthquakes or wind and gusts. In order to minimize the overall torsion, it is imperatively necessary to reduce the distance between the centre of mass (CM) and centre of stiffness (CS) in the design stage. In this context, the main purpose of this paper is to present a theoretical method of reducing torsion by minimizing the distance between CM and CS at the level of each floor of the structure. Principal stiffness axes are also changed in convenient directions so that the movement of the structure leads to a favourable plastic mechanism in the fundamental mode of vibration. To achieve the goal, the main objective is to change the dimensions and orientations of the pillars located on the perimeter of the structures. The described method was used to study: irregular shaped structures in plan; structures with stairs or with central concrete core; structures with elevation retractions. The overall torsion reducing was achieved with Matlab programs, and the verification of the results was carried out by using the software ETABS 2016.